(untitled) (Journal of Medical & Health Sciences Review, 2026)
Hyper-vascular liver metastasis lesions are very common in primary malignancies like colorectal and gastrointestinal cancers and constitute a significant source of diagnostic dilemma in normal clinical practice. Early and accurate identification of these lesions is critical towards proper staging of tumors, treatment and prognosis of patients. Triple Phase Computed tomography is believed to be a reliable imaging modality in detecting liver metastases due to the capability of showing vascular features in the various phases of contrast. Nonetheless, the clinical practice of it is frequently hampered by excessive cost, technical demands, and limited provision, especially in healthcare facilities with low resources. Ultrasonography on the contrary is highly accessible, noninvasive, and cheaper, however, its diagnostic capability against hyper-vascular liver lesions varies significantly and may be operator-dependent. The study set out to compare the diagnostic and patient-reported confidence of Triple Phase CT-Scan and Ultrasonography in the detection of hyper-vascular lesions of liver metastasis. Three hospitals were sampled by a cross-sectional study (20-80 years), which involved 45 patients with suspected or confirmed liver metastases. Each of the participants was subjected to both radiographic tests. The imaging findings were evaluated to obtain sensitive and specificity of each modality, and patient satisfaction and confidence were measured with the help of the structured questionnaires. These findings showed that Triple Phase CT-Scan was effective in the number of hyper-vascular lesions detected (84.4% of cases) as compared to the detection rate of Ultrasonography (86.7%). Although the similarity was observed in the lesion detection rates, Triple Phase CT-Scan recorded a higher specificity of 64.4% versus 46.7% of Ultrasonography. Moreover, 48.9% of the patients have chosen Triple Phase CT-Scan because of better visualization of lesions and higher confidence of making a diagnosis. To sum up, Triple Phase CT-Scan is a more specific and generally reliable in diagnostic power in hyper-vascular lesions of liver metastasis. Even though the Ultrasonography is a useful tool in the first-line screening particularly in resource-constrained conditions, a combination of imaging methods can be helpful in improving diagnostic performance. Future research concerns should be on low-cost imaging approaches and patient outcomes over time with respect to early diagnosis.